Optimal Sitting and Sizing of PV Generation Connected to the Radial Distribution Feeders - Lincy, G; M. Ponnavaikko, Dr; Lenin Anselm W.A, Dr (International Journal of Engineering and Technology, 2018)
Electricity is a basic need for the daily life of everyone, and it serves as the main driver for the economic growth in any country. Coal-fired Electricity generation forms the major share of energy resources in the world.Â Â In India, Coal-fired electricity generation represents about 78% of the total power generation in the country. Coal reserve is fast depleting in the world. This situation has necessitated many countries in the world to opt for Distributed Generation (DG), using renewable sources of energy, to meet, the growing demand for electricity and to meet the depleting situation of Coal. In the past, some studies have been carried out by the Researchers using different types of DG systems. This study considers installation of PV systems, making use of the abundant availability of Solar Energy Resources. Appropriate sitting and sizing of DGs could lead to many positive effects for the distribution systems concerned. However, at the same time, inappropriate sitting and sizing of DGs could lead to many negative effects on the distribution systems concerned, such as the voltage profiles, beyond permissible limits and increased network losses. Therefore, it becomes necessary to allocate DGs at optimal locations with optimal sizing. This paper presents the results of the study carried out in a 400 V distribution system as well as in an 11-kV feeder in the Kanchipuram Distribution System in Tamil Nadu, India. This paper also presents the economic impact of the system with PVCs regarding Internal Rate of Return (IRR)for the investment made.Â